Isotropic Potential Model of Hydrogen Physisorption on Exohedral of Single Walled Carbon Nanotubes with Various Diameter - Nasruddin Nasruddin; Engkos Kosasih; Supriyadi Supriyadi; Ihsan Zulkarnain (President University, 2016)
Abstract. This work presents step-by-step procedure of modeling accurate interaction potential energy between hydrogen and outer surface of zigzag Single Walled Carbon Nanotube (CNT) as a function of its diameter. First principles calculations at MP2 method level and def2-SVP basis-set were performed to predict the interaction potential energy of hydrogen gas molecule on outer surface of CNT cluster model. The result shows that the physisorption energy is ranging between 1.05 kcal/mol to 1.14 kcal/mol. Using force-matching method, Lennard-Jones potential parameters were approximated for interaction between united-atom model of hydrogen molecules and the CNT. Assuming constant σ = 3.2 Å, the result shows that the ε parameter can be defined as a function of CNT diameter.Keywords. Hydrogen, Carbon Nanotube, First principles, Ab initio, Binding Energy, Force-matching Method, Lennard-Jones Potential